KETERGANTUNGAN MASYARAKAT TERHADAP HUTAN LINDUNG DALAM PROGRAM HUTAN KEMASYARAKATAN - Reni Haryani; R Rijanta (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2019)
One program issued that is held by the Ministry of Environment and Forestry related to empowering communities is the Community Forestry program, which one is located in Kalibiru sub-village, Kulon Progo Regency. This study aims to determine the activities of community dependence on CF land and the factors that influence community’s forest dependency level of Mandiri HKm farmer group on forest resources that are on the land after developing natural tourism. Respondents was conduted in a survey of all members of the forest farmer group. Data collected through intervews and field observations were analyze descriptive qualitatively. The results showed that the form of dependence carried out by the community was the fufillment of food, fodder collection, the use of wood ad bamboo, rhizome plants harvesting, and the development of natural tourism. The level of dependence of respondents on HKm land is relatively low because of several factors such as age, level of eudcation, the main job, number of family dependents, the ownership of a narrow land, distance forest from house, HKm land use, forest use utilization, and HKm land contribute to farmes’s income. The existence of ecotourism reduces the level of community dependence on protected forests.